Pyroptosis-Related Gene to Construct Prognostic Signature and Explore Immune Microenvironment and Immunotherapy Biomarkers in Bladder Cancer - Zhang, Xiangyu; Liang, Hengzhang; Tang, Qi; Chen, Hongyi; Guo, Fangzhou (Frontiers in Genetics, 2022)
Bladder cancer is the most common malignant tumor in the urinary system with a poor prognosis; new drug targets are urgently needed. Pyroptosis is defined as programmed cell death in the inflammatory form mediated by the Gasdermin protein. It has therapeutic potential in the synergistic effect of radiotherapy and chemotherapy, reversal of chemotherapy resistance, regulation of body environment to affect tumor metabolism, and enhancement response rate of the immune checkpoint inhibitor. This study aims to explore the role of pyroptosis in bladder cancer. A prognostic model based on 5 pyroptosis-related genes was constructed by univariate Cox survival analysis and LASSO regression analysis，using The Cancer Genome Atlas(TCGA) cohort. Patients were divided into high and low-risk groups according to the median risk score, all of the 5 PRGs were downregulated expression in the high-risk group. The high-risk group had a worse prognosis than the low-risk group, and survival differences between the two groups were also validated in the Gene Expression Omnibus (GEO)cohort. And the ROC curves present that the model has a moderate predictive ability. Univariate and multivariate Cox regression analysis for clinical characteristics and risk score indicted risk score is an independent prognosis factor for OS of BC patients. In addition, the high-risk group was associated with advanced N and TNM stages.GO and KEGG analysis found that the antigen processing and presentation of exogenous antigen, exogenous peptide antigen, peptide antigen were enriched in the low-risk group. A higher abundance of tumor-infiltrating immune cells and more active immune pathways were also found in the low-risk group.In addition,immunotherapy biomarkers including TMB,PD1,PD-L1,CTLA4 and LAG3 had higher levels in the low-risk group. This suggests that patients in the low-risk group may be potential responders to the immune checkpoint inhibitors.